Metabolic profiling of idiopathic pulmonary fibrosis in a mouse model: implications for pathogenesis and biomarker discovery - Zhang, Yu-zhu; Jia, Xiu-juan; Xu, Wen-juan; Ding, Xiao-qian; Wang, Xiao-meng; Chi, Xiao-sa; Hu, Yi; Yang, Xiao-hui (Frontiers in Medicine, 2024)
Alterations in metabolites and metabolic pathways are thought to be important triggers of idiopathic pulmonary fibrosis (IPF), but our lack of a comprehensive understanding of this process has hampered the development of IPF-targeted drugs. To fully understand the metabolic profile of unsaturated fatty acids, pentose phosphate pathway, and alanine, aspartate, and glutamate metabolism. Seven metabolites were screened by machine learning LASSO models and evaluated as ideal diagnostic tools by receiver operating characteristic curves (ROCs). In conclusion, the serum metabolic disorders found to be associated with pulmonary fibrosis formation will help to deepen our understanding of the pathogenesis of pulmonary fibrosis.